Assessing business activity of the Russian industry - A. S. Dikarev (Вестник университета)
The relevance of the study is due to the fact that, despite the difﬁcult economic and political situation for the Russian industry and the economy as a whole, there are problems not only with the arrival of foreign raw materials and goods in the domestic market, but also with the smooth operation of industry. It is necessary to develop and form new, more essential approaches to the industrial development strategy in the conditions of forced modernization of the industry. The factors that have the greatest and the least inﬂuence on the business activity of enterprises have been identiﬁed. The directions for forming new ways of domestic industry effective development through assessing the entrepreneurial conﬁdence index on the part of enterprises of extractive and manufacturing industries have been analyzed. As the index evaluation result, the author concludes that the level of enterprises’ business activity has jumping values, in the course of which the factors that have a negative impact on industrial production development have been identiﬁed.